2018
DOI: 10.1093/pubmed/fdy046
|View full text |Cite
|
Sign up to set email alerts
|

Peripheral arterial disease in Scottish military veterans: a retrospective cohort study of 57 000 veterans and 173 000 matched non-veterans

Abstract: The findings provide evidence for a hidden burden of life- and limb-threatening PAD in older veterans and are consistent with the higher rates of military smoking which have been reported previously. The study emphasizes the need for vascular preventive measures in this group.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 35 publications
1
5
1
Order By: Relevance
“…both in earlier study 6 and confirmed in this up, but that paradoxically fewer amputations take place in veterans with PAD than non-veterans. We suggest that this may be due to earlier presentation, and hence greater likelihood of limb-saving treatment, as veterans may be less likely to ignore the symptoms of claudication than non-veterans.…”
Section: Original Researchsupporting
confidence: 77%
See 1 more Smart Citation
“…both in earlier study 6 and confirmed in this up, but that paradoxically fewer amputations take place in veterans with PAD than non-veterans. We suggest that this may be due to earlier presentation, and hence greater likelihood of limb-saving treatment, as veterans may be less likely to ignore the symptoms of claudication than non-veterans.…”
Section: Original Researchsupporting
confidence: 77%
“…3 A study of US veterans showed that 63% of amputations between 1989 and 1998 were for diabetes and 24% for peripheral vascular disease, with overall age-specific rates for veterans exceeding those in the general US population. 4 5 We have shown that Scottish veterans are at increased risk of PAD compared with the wider population, 6 but we had no information on whether this was associated with an increased incidence of limb loss.…”
Section: Introductionmentioning
confidence: 99%
“…Despite the theoretical increased risk of dementia in veterans based on their known increased risks of cardiovascular disease (Bergman et al, 2014(Bergman et al, , 2018, PTSD (Iversen et al, 2009) and traumatic/mild traumatic brain injury (Shively & Perl, 2012), reassuringly we find no evidence to support the hypothesis that veterans are at an increased risk of dementia overall in comparison with people who have never served. The veterans in our study were aged up to 73 years at the end of data collection, and therefore emerging differences might have been expected to become apparent.…”
Section: Main Findingscontrasting
confidence: 77%
“…2 We have previously reported that a cohort of 57 000 veterans in Scotland who were born between 1945 and 1985, followed up for over 30 years to 2012, were at increased risk of acute myocardial infarction in comparison with 173 000 age-matched, sex-matched and geographically matched non-veterans. 3 We also found that the same cohort was at increased risk of peripheral arterial disease, 4 smoking-related cancers 5 and chronic obstructive pulmonary disease. 6 We suggested that this was likely to be due to the well-documented higher rates of smoking which have been reported in serving military personnel over many years.…”
Section: Introductionmentioning
confidence: 59%